Lifestyle factors and hyperuricemia risk: a prospective cohort study of 14,635 participants examining the protective role of daily stair climbing - Yin, Wenkui; Luo, Donglin; Huang, Wenying; Jiang, Haichao; Wang, Yahai; Qi, Haixia (Frontiers in Nutrition, 2025)
BackgroundThis study aimed to explore the association between daily stair climbing and the risk of hyperuricemia and to investigate the potential mediating role of blood lipid biomarker levels in this association.MethodsThis study is a prospective cohort study from the UK Biobank, including 14,635 participants. Participants were categorized based on their self-reported daily stair climbing habits and the presence of hyperuricemia, which was defined as serum uric acid concentration > 420 μmol/L for men and > 360 μmol/L for women. Blood lipid biomarker levels were assessed as potential mediators. We used a mediation analysis framework to estimate the direct and indirect effects of daily stair climbing on hyperuricemia risk. All analyses were conducted using R Studio version 4.2.3. Statistical significance was defined as a two-sided p-value of < 0.05.ResultsOverall, compared to the no stair climbing group, with full adjustment, we observed a significant negative correlation between participants who climbed 160 to 200 steps of stairs daily and hyperuricemia; the HRs were 0.70 (95% CI: 0.51–0.95, p = 0.024). Mediation analysis revealed a significant indirect effect of stair climbing (160–200 steps/day) on the risk of hyperuricemia, mediated through high-density lipoprotein cholesterol and triglyceride levels, with mediation proportions of 27.6 and 21.8%, respectively (p < 0.001).ConclusionDaily stair climbing is associated with a reduced risk of hyperuricemia, and this relationship may be partially mediated by alterations in high-density lipoprotein cholesterol and triglyceride levels. These findings suggest that promoting daily physical activity, such as stair climbing, may be an effective strategy for managing uric acid levels and reducing the risk of hyperuricemia.